2019
DOI: 10.1111/ijlh.13019
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic evaluation of hereditary erythrocytosis: Pathways and caveats

Abstract: Multiple algorithms have been published for the evaluation of hereditary erythrocytosis (HE). Typical entry points begin after excluding the more common acquired conditions through investigations of clinical history and assessment of cardiac, pulmonary, or vascular system disorders. Prior exclusion of JAK2 mutations, particularly the common JAK2 V617F mutation, is indicated in adults but less so in pediatric populations. Key decision trees are based on serum erythropoietin levels and p50 results. Recent data r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…JAK2 genetic testing was performed in all of our patients and serum EPO level in 96%. After a thorough documentation review of all patients secondary erythrocytosis was found in 34/116 (29%) patients, 15/116 (13%) remained idiopathic despite adequate diagnostics, whereas a quite high number of patients, 67/116 (58%) would need further investigations for characterisation of erythrocytosis according to modern diagnostic algorithms [ 2 4 , 11 , 28 ]. It seems that patients with non-clonal erythrocytosis were not considered at high risk for complications and therefore were not referred for further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JAK2 genetic testing was performed in all of our patients and serum EPO level in 96%. After a thorough documentation review of all patients secondary erythrocytosis was found in 34/116 (29%) patients, 15/116 (13%) remained idiopathic despite adequate diagnostics, whereas a quite high number of patients, 67/116 (58%) would need further investigations for characterisation of erythrocytosis according to modern diagnostic algorithms [ 2 4 , 11 , 28 ]. It seems that patients with non-clonal erythrocytosis were not considered at high risk for complications and therefore were not referred for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Patient referral to the haematologist is often based on repeated complete blood count (CBC) without a thorough history, physical examination, or additional laboratory testing. It is important to be familiar with the contemporary evaluation of erythrocytosis, utilizing algorithms for efficient testing in the majority of patients in everyday clinical practice [2][3][4][5]11]. Whereas PV is almost always easily confirmed, other types of erythrocytosis are often less well recognized, weakly proven or even ignored [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in less than 5% of a and b hemoglobin variants with high oxygen affinity (HOA HGB), normal or slightly decreased P 50 may be observed. P 50 value is normal in patients with erythrocytosis and BPGM mutation, as well [9][10][11][12].…”
Section: Mutations Of Oxygen-sensing Pathways Genesmentioning
confidence: 95%
“…Primary erythrocytosis involves alteration in the erythropoietin (EPO) receptor (EpoR) either through an acquired or congenital process [ 3 ]. Patients with primary erythrocytosis generally have low levels of EPO and normal oxygen dissociation curves [ 4 ]. The most common acquired process is polycythemia vera, which is driven by a somatic mutation in the JAK2 signaling pathway of the EpoR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%